ANALISIS PRIORITAS PENGEMBANGAN KAWASAN ANDALAN DI DESA KARANG INDAH KECAMATAN MANDASTANA - ZUMROTUN NISA AS; MUHAMMAD ANSHAR NUR (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The aims of this research are to (1) Find out how contribution of each criteria to the development of a mainstay area In The Karang Indah (2) to find out the potential of what is a priority to be developed into a mainstay in the village of Karang Indah districs of Mandastana. The respondents of this research are 10 which are considered to influence the determination of mainstay in the Village of Karang Indah districs of Mandastana, that can be used in data processing. Data is processed by using AHP (Analytical Hierarchy Process) .The result of this research showed that the alternative criteria of the regional potential, regional policy, per capita income, and employment opportunities are influence the determination priority of mainstay area development, by the value of preference in order are: 54% regional potential, 23% of regional policy, 14% per capita income, and 9% of employment opportunities. Based on the alternatif criteria the selection of priority development area mainstay are  58% horticulture of the plants of orange, a combination or Agro-education 30% and 12% of English-Village. the conclusion of this research is, that the most dominant sector is the horticulture of the plants of oranges (58%).Keywords:     Mainstay Area, Horticulture of the Plants of Orange, English Village, Agro-Education , AHP (Analytical Hierarchy Process) Method